Diastolic Blood Pressure is a Risk Factor for Peri-procedural Stroke Following Carotid Endarterectomy in Asymptomatic Patients. (May 2017) - de Waard, D.D.; de Borst, G.J.; Bulbulia, R.; Huibers, A.; Halliday, A.; ,
Abstract : Objective/Background: Carotid endarterectomy (CEA) prevents future stroke, but this benefit depends on detection and control of high peri-operative risk factors. In symptomatic patients, diastolic hypertension has been causally related to procedural stroke following CEA. The aim was to identify risk factors causing peri-procedural stroke in asymptomatic patients and to relate these to timing of surgery and mechanism of stroke. Methods: In the first Asymptomatic Carotid Surgery Trial (ACST-1), 3, 120 patients with severe asymptomatic carotid stenosis were randomly assigned to CEA plus medical therapy or to medical therapy alone. In 1, 425 patients having their allocated surgery, baseline patient characteristics were analysed to identify factors associated with peri-procedural (< 30 days) stroke or death. Multivariate analysis was performed on risk factors with a p value < .3 from univariate analysis. Event timing and mechanism of stroke were analysed using chi-square tests. Results: A total of 36 strokes (27 ischaemic, four haemorrhagic, five unknown type) and six other deaths occurred during the peri-procedural period, resulting in a stroke/death rate of 2.9% (42/1, 425). Diastolic blood pressure at randomisation was the only significant risk factor in univariate analysis (odds ratio [OR] 1.34 per 10 mmHg, 95% confidence interval [CI] 1.04–1.72; p  = .02) and this remained so in multivariate analysis when corrected for sex, age, lipid lowering therapy, and prior infarcts or symptoms (OR 1.34, 95% CI 1.05–1.72; p  = .02). In patients with diastolic hypertension (> 90 mmHg) most strokes occurred during the procedure (67% vs. 20%; p  = .02). Conclusion: In ACST-1, diastolic blood pressure was the only independent risk factor associated with peri-procedural stroke or death. While the underlying mechanisms of the association between lower diastolic blood pressure and peri-procedural risk remain unclear, good pre-operative control of blood pressure may improve procedural outcome of carotid surgery in asymptomatic patients.